(untitled) (LIS TODAY, 2023)
The main aim of this research paper is to find out use, advantages and problems faced by the library and information professionals in West Bengal in marketing through social media. For this study thirteen (13) college libraries in West Bengal were selected as a research sample. The findings of this research proved that most of the college libraries use WhatsApp, Facebook, Instagram, Twitter, and LinkedIn for publicity of library services. Most of the libraries use social media for marketing library resources and services, for circulating library news and events for research purpose. A face-to-face interview method are used for data collection in this study. Library professionals gives their important views and suggestions about ways of promoting library services through social media.